Principles of vibration - Tongue, Benson H. (Oxford University Press, 2002)
In this second edition of Principles of Vibration, Benson H. Tongue takes a refreshingly informal approach to the understanding and analysis of vibration problems. His student-friendly style creates a sense of "one-on-one" communication to which students respond with enthusiasm, declaring that the text is enjoyable, informative, and even "good bedtime reading." The text material can be used in a first vibrations course and in advanced undergraduate/beginning graduate courses. Some familiarity with linear algebra, elementary deformable bodies, and beginning dynamics is assumed. Tongue provides a basic understanding of the principles of vibrations, presenting the core ideas and theories that define the field. Starting with classical material--single-degree-of-freedom systems--he branches out into modern topics, emphasizing multiple-degree-of-freedom systems. Principles of Vibration, Second Edition is an ideal text for senior undergraduates and graduate students in mechanical, civil, and aeronautical engineering departments